Influence of the granulometry and fiber content of palm residues on the diesel S-10 oil sorption in polyurethane /palm fiber biocomposites - Martins, Larissa S.; Monticelli, Francisco Maciel [UNESP]; Mulinari, Daniella R. (Elsevier, 2020)
The use of technologies with sustainable adsorbents from agro-industrial residues with hydrophobic characteristics has induced the interest of the scientific community, due to the accidents involving spills and leaks of organic pollutants, generating the concern impacts caused to the environment. Thus, in this study was proposed an alternative for palm residues as reinforcing in castor oil-based polyurethane, obtaining eco-friendly biocomposites for sorption of S10 diesel oil. Biocomposites were obtained by mass mixing the polyol with the prepolymer (1:1) and reinforced from 5 to 20% m/m with palm residues and different particle sizes (28 mesh and 35 mesh), to evaluate the influence of same. The palm residues, pure PU, and biocomposites were characterized by techniques scanning electron microscopy (SEM), optical microscopy (OM), apparent density, porosimetry (BET), contact angle, X-ray diffractometry (XRD), thermogravimetry (TGA), and spectroscopy infrared (FTIR). To evaluate the sorption capacity and efficiency as a function of the content and particle size of the fiber added to the polymeric matrix, tests were performed in times of 30–240 ​s in three systems: S10 diesel oil, S10 diesel oil/saline water and S10 diesel oil/mineral water. Results showed that biocomposites presented greater capacity and better sorption efficiency compared to pure PU in the three sorption systems analyzed; however, a greater performance was obtained in the S10 diesel oil system. Besides, the fiber content and particle size directly influenced the results. Biocomposites with higher particle size fibers (28 mesh) and higher content showed the best results with sorption capacity (10.02 ​g/g) and sorption efficiency (24.10%). The contour diagram showed that different particle size fiber (28 and 35 mesh) in the biocomposites presented a linear trend between the sorption/time/fiber fraction. Also, biocomposites presented a reuse efficiency of five cycles, maintaining their hydrophobicity even after the process.
Keywords: Castor oil; Diesel oil sorption; Palm residues; Polyurethane